In Vitro Evaluation of Shear Bond Strength of Sapphire Brackets after Dental Bleaching - Zainab M Kadhom (College of Dentistry/ University of Baghdad, 2016)
Background: The present study was conducted to evaluate the effects of different bleaching methods on the shear bond strength of orthodontic Sapphire brackets bonded to human premolars teeth using light cured composite resin and to determine the predominant site of bond failure. Materials and Methods: Thirty freshly extracted human premolars were selected and randomly divided into three groups (10 per group). These groups are: control (unbleached) group, hydrogen peroxide group (HP) 37.5% ; which is the in- office bleaching method group, carbamide peroxide group (CP) 16%; which is the at- home bleaching method group. After bleaching process was performed, all the teeth stored in distilled water in a sealed container at room temperature for 24 hours before bonding was initiated, then orthodontic brackets were bonded with a light cure composite resin, stored in distilled water at room temperature for another 24 hours before debonding then the brackets de-bonded and tested for shear bond strength using an Instron universal testing machine. For adhesive remnant index (ARI) the enamel surface and bracket base of each tooth were inspected under magnifying lens (20X) of a stereomicroscope. Results and Conclusions: Non-statistically significant differences of shear bond strengths were found between the control group and the bleached groups, the dental bleaching in both methods did not affect the SBS of Sapphire brackets. The mode of failure was mostly between the adhesive and the enamel and the bond failure between the bracket base and the adhesive were also observed. Keywords: Shear bond strength, tooth bleaching agents, orthodontic brackets, dental bonding.